Christian Conversion as Attitude Change: Contributions to a Phenomenology of Conversion - Rubio, Roberto (2024)
This paper attempts to contribute to the studies of phenomenological philosophy dealing with religious conversion. Our contribution is to describe Christian conversion in phenomenological terms as attitude change; or, more precisely, as the transition from natural attitude to religious Christian attitude. The description is focused on the noetic pole of experience, especially considering the relationship between faith in the daily perceptual world, on the one side, and Christian faith in God, on the other side. Additionally, we present some challenges proper of the philosophical-phenomenological approach. On the one hand, we consider the challenges pertaining to the philosophical-phenomenological approach as such; on the other hand, we present the challenges that emerge when considering approaches that originate from other disciplines, such as Sociology or the Anthropology of Religion.